Clinical profile, morbidity, and outcome of adult‐onset generalized pustular psoriasis: analysis of 102 cases seen in a tertiary hospital in Johor, Malaysia. (22nd August 2013) - Choon, Siew Eng; Lai, Nai Ming; Mohammad, Norshaleyna A; Nanu, Nalini M; Tey, Kwee Eng; Chew, Shang Fern
Abstract Background Generalized pustular psoriasis (GPP) is a severe but rare variant of psoriasis. Our objective is to review the clinical profile, comorbidities, and outcome of patients with GPP. Materials and methods A retrospective note review of all patients with adult‐onset GPP. Results A total of 102 patients with adult‐onset GPP were diagnosed between 1989 and November 2011, with a female to male ratio of 2 : 1. The mean age at onset of GPP was 40.9 years (range: 21–81 years). Acute GPP was the most common variant seen (95 cases), followed by four localized variants of GPP and three with annular pustular psoriasis. Fever and painful skin were present in 89% of patients, arthritis in 34.7%, and leukocytosis in 78.4%. Common triggers were systemic steroids (45 cases), pregnancy (17 cases), and upper respiratory tract infections (16 cases). A positive family history of psoriasis and GPP was present in 29% and 11%, respectively. Comorbidities included obesity (42.9%), hypertension (25.7%), hyperlipidemia (25.7%), and diabetes mellitus (23.7%). The mean duration of admission and pustular flare for acute GPP was 10.3 days (range: 3–44 days) and 16 days (range: 7–60 days), respectively. Fifty‐four patients responded to systemic retinoid, 21 to methotrexate, eight to cyclosporine, and one to adalimumab, but recurrences were common. Conclusions Our study confirms the poor response of GPP to currently available anti‐psoriatic agents, with frequent flare‐ups. There is a need for a more effective targeted therapy for this condition.